CONTRAST-INDUCED NEPHROPATHY IN PATIENTS WITH STABLE CORONARY ARTERY DISEASE AND 1-YEAR PROGNOSIS - O. Iu. Mironov; O. A. Sivakova; V. V. Fomin (Евразийский Кардиологический Журнал, 2020)
Aim. The aim of our study was to assess the prevalence of contrast-induced nephropathy (CIN) in patients with chronic coronary artery disease (CAD) and its 1-year prognostic significance.Materials and methods. 462 patients with chronic CAD and indications to the interventions with intraarterial contrast media administration were included in the study. We conducted a prospective open cohort study (ClinicalTrials.gov NCT04014153). The primary endpoint was the development of CIN. The secondary endpoints were total mortality, cardiovascular mortality, myocardial infarction, stroke, gastrointestinal bleeding, acute decompensation of heart failure, coronary artery bypass grafting, repeat percutaneous coronary intervention.Results. 28 patients (6%) developed CIN. The rate of CIN in female patients was twice higher, than in males (9,29% vs. 4,66%). There was a trend towards less cases of CIN in patients without obesity (5,88% vs. 6,22%). CIN developed more frequently in patients with anemia (8,9% и 5,7%, р=0,3649, ОR 1,633,95% CI 0,6507-4,239). There was a trend to higher incidence of CIN in people with hyperuricemia (8% vs. 5,95%, р=0,6575, ОR 1,375,95% CI 0,3055-5,808). The rate of CIN in patients with diabetes mellitus was 2% higher, then without one. People, who suffered from myocardial infarction after 1 year of follow up, had the highest rate of CIN (26,7%), as well as patients with other major cardiovascular complications (18,1%). The rate of repeat percutaneous coronary interventions was 9,5%, the rate of acute decompensation of heart failure was 7%.Conclusion. The prevalence of CIN in patients with chronic CAD was 6%. After 1 year of follow up the rate of CIN was higher in patients who had myocardial infarction, repeat percutaneous coronary interventions and acute decompensation of heart failure.